Mysterious attendance cycles in Cory’s shearwater, Calonectris diomedea: An exploration of patterns and hypotheses - Granadeiro, José Pedro (2009)
Several species of seabirds show cyclic patterns of attendance at their nesting colonies.We examined the patterns of variation in the numbers of Cory’s shearwater at three colonies (two oceanic and one located on the continental shelf), including the world’s largest, at Selvagem Grande, Madeira, Portugal and considered several hypotheses concerning their causal mechanisms. At Selvagem Grande, cycles were exceptionally marked and regular, with a periodicity ranging from 7.8 to 11 days, and involved both breeders and nonbreeders. In contrast, variation in numbers was aperiodic at a nearby and much smaller colony (Selvagem Pequena), and also at the colony located off the Portuguese coast (Berlenga Island).We found no relationships between number of birds ashore and environmental variables such as wind direction and speed or lunar cycle. Cycles did not seem to be driven by oscillations in food availability or accessibility, given that they did not correlate with daily chick growth rates (which were acyclic) or diet. Despite their regularity, cycles were slightly out of phase in different sectors of Selvagem Grande, which suggests that social interactions at the colony could act as an entrainment agent for an endogenous rhythm, and so cycles are probably more likely to occur in large and dense colonies. Observations are consistent with the hypothesis that cycles facilitate social interactions by maximizing the probability of encounters at the colony. However, the exact mechanisms through which these remarkable cycles are controlled are still completely unknown, and clearly further research is needed.